Seeing action simulation as it unfolds: The implicit effects of action scenes on muscle contraction evidenced through the use of a grip-force sensor. (June 2018) - Blampain, J.; Ott, L.; Delevoye-Turrell, Y.N.
Abstract: Action simulation is a cognitive process that mentally simulates a motor act without performing it in the true external world. Simulation mechanisms play a key role in perceiving, feeling and understanding actions executed by others. However, very little is known about the process dynamics because of the absence of a behavioral tool to probe directly the action simulation process as it unfolds. Twenty-seven healthy adults were required to hold a force sensor in a relaxed pinch-grip while viewing action videos of different intensities: wait (null); touch (low); move (medium); crush (high). When contrasting the variations in grip force (GFv) across conditions, results indicated that GFv started to increase and peaked respectively 200 and 400 ms after the moment of effector-object contact. In the wait condition, GFv remained flat throughout the trial confirming an absence of simulation engagement. Peak GFv was greater for the high and medium than for the low intensity videos suggesting greater brain activity overflow to the peripheral motor system when simulating more effortful body movements. These effects were negatively correlated with the motor imagery abilities of the participants, with greater GFv in the poor imagers as determined by the Movement Imagery Questionnaire. Our results confirm the possibility of using a non-invasive grip force sensor to detect not only when individuals are cognitively engaged in action simulation but also to reveal the dynamics of the process. With various sets of videos, this paradigm offers new perspectives in the study of action simulation and its role in human cognition. Highlights: A grip sensor can probe the brain activity overflow to the motor system during action simulation. Micro variations in grip force are observed when participants engage in a simulation process without overt movement. Greater micro-variations of grip force are measured when simulating body movements of greater intensity. The behavioral consequence of action simulation takes 200–400 ms to develop fully. The simulation process is time stamped to motor goal.